2011
DOI: 10.1098/rsif.2011.0733
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical responsiveness of the endothelial cell of Schlemm's canal: scope, variability and its potential role in controlling aqueous humour outflow

Abstract: Primary open-angle glaucoma is associated with elevated intraocular pressure, which in turn is believed to result from impaired outflow of aqueous humour. Aqueous humour outflow passes mainly through the trabecular meshwork (TM) and then through pores formed in the endothelium of Schlemm's canal (SC), which experiences a basal-to-apical pressure gradient. This gradient dramatically deforms the SC endothelial cell and potentially contributes to the formation of those pores. However, mechanical properties of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
108
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(117 citation statements)
references
References 82 publications
7
108
1
Order By: Relevance
“…In this study, we confirmed that Klf4 is upregulated in flow-exposed dermal BECs and LECs in vitro and in developing SC ECs in vivo (28,54). Moreover, previous studies indicated that even if the current of aqueous humor is low, the presence of AHO itself is enough to actively modulate the behaviors of SC ECs, which is in agreement with our data (15). We demonstrated that Prox1 and Klf4 expressions in SC are simultaneously modulated in a temporal manner and are associated with AHO levels during developmental stage and adulthood.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…In this study, we confirmed that Klf4 is upregulated in flow-exposed dermal BECs and LECs in vitro and in developing SC ECs in vivo (28,54). Moreover, previous studies indicated that even if the current of aqueous humor is low, the presence of AHO itself is enough to actively modulate the behaviors of SC ECs, which is in agreement with our data (15). We demonstrated that Prox1 and Klf4 expressions in SC are simultaneously modulated in a temporal manner and are associated with AHO levels during developmental stage and adulthood.…”
Section: Discussionsupporting
confidence: 82%
“…SC controls the ocular tissue fluid homeostasis and tissue pressure by functioning as a major draining channel. Furthermore, the junction between SC ECs and trabecular meshwork (TM) is composed of a specialized tethering structure, which is responsible for providing an appropriate pressure gradient across the inner wall of an SC to maintain the integrities of SC ECs, thereby providing a tissue pressure-sensing/responding mechanism, such as anchoring filaments for LVs (14)(15)(16).…”
Section: Introductionmentioning
confidence: 99%
“…An increased resistance to flow in the conventional pathway (which carries up to 90% of the total aqueous humor out of the eye) is predominantly responsible for the elevated IOP in many types of glaucoma. In primary open-angle glaucoma (POAG), the most common type, increased outflow resistance has been classically associated with the juxtacanalicular portion of the TM mediated through the extracellular matrix (ECM) as well as in the endothelial-lined SC (21,22) . Morphologically, the TM is a complex tissue consisting of TM cells, ECM, and empty spaces, which the aqueous humor runs through.…”
Section: Physiology Of Aqueous Humor Outflowmentioning
confidence: 99%
“…84,90 In addition, LPA has been reported to increase SC cell stiffness and intracellular calcium levels. 19,42 Interestingly, myocilininduced anti or de-adhesive interactions in TM cells have been found to be suppressed in the presence of LPA. 91,92 LPA has been demonstrated to increase SC cell permeability barrier activity by following the diffusion of horse radish peroxidase using the transwell cell culture system.…”
Section: Lysophospholipids In Regulation Of Ah Outflow and Iopmentioning
confidence: 99%
“…[13][14][15][16][17][18] It is also widely believed that changes such as tissue stiffness due to altered cellular contraction, oxidative damage, and altered metabolic activity of TM tissue are associated with increased resistance to AH outflow and elevated IOP. 13,[19][20][21][22][23] Little is known, however, about the cellular and molecular mechanisms that drive the increase in resistance to AH outflow and trigger the associated changes in glaucomatous eyes.…”
Section: Introductionmentioning
confidence: 99%